2011 Clinical Practice Guidelines for Type 2 Diabetes in Korea - Ko, Seung-Hyun; Kim, Sung-Rea; Kim, Dong-Joon; Oh, Seung-Joon; Lee, Hye-Jin; Shim, Kang-Hee; Woo, Mi-Hye; Kim, Jun-Young; Kim, Nan-Hee; Kim, Jae-Taik; Kim, Chong Hwa; Kim, Hae Jin; et al. (Diabetes & metabolism journal, 2011)
As in other countries, type 2 diabetes is major health concern in Korea. A dramatic increase in the prevalence of type 2 diabetes and its chronic complications has led to an increase in health costs and economic burdens. Early detection of high risk individuals, hidden diabetic patients, and improvement in the quality of care for the disease are the first steps to mitigate the increase in prevalence. The Committee of Clinical Practice Guidelines of the Korean Diabetes Association revised and updated the '3rd Clinical Practice Guidelines' at the end of 2010. In the guidelines, the committee recommended active screening of high risk individuals for early detection and added the hemoglobin A1c level to the diagnostic criteria for type 2 diabetes based on clinical studies performed in Korea. Furthermore, the committee members emphasized that integrating patient education and self-management is an essential part of care. The drug treatment algorithm based on the degree of hyperglycemia and patient characteristics were also updated.